The use of Nature-based Solutions (NbS) in pineapple and banana, value chains in Sarapiquí River Basin, Costa Rica - Gamboa-Agüero, Marcelo (2026)
Introduction. Nature-based Solutions (NbS) represent viable options for addressing management challenges in the production and processing of pineapple, banana, and plantain. There are corporate clusters for these fruit crops within the Sarapiquí River Basin (SRB), an area facing increasing environmental pressure and problems. Currently, NbS incorporating processes into these value chains within the basin remains unknown. Objective. To analyze the integration of NbS for phytopathological and hydrological risk management across different fruit-producing and processing firms in the SCR. Methodology. Currently research was based on an empirical, exploratory, and descriptive case study, utilizing a qualitative approach centered on the SRB. All producing and/or processing companies were surveyed (24 companies). From June to October 2025, farm management systems were observed, and semi-structured interviews were conducted with managers of voluntarily participating companies. A thematic inductive method was used for the analysis of the interviews. Analysis. Company’s participation was quite limited (9 interviewed out of 24), showing a marked sectoral difference (6 of 21 in pineapple; 3 of 5 in banana or plantain). Extensive use of conventional practices was observed on pineapple farms. The few pineapple companies interviewed showed a heterogeneous incorporation of Nature-based Solutions (NbS), with greater progress observed in those oriented towards organic production, integrated management, preinvestment in NbS, and those with foreign capital (mainly as biocontrolling agents’ approach). Banana producers were multinational companies with research and development in specific NbS. Conversely, the two interviewed processing companies (1 pineapple, 1 banana/plantain) showed no interest in NBS. Conclusion. In producer companies, the incorporation of NbS is limited in pineapple operations, but advanced in banana operations. In the processing companies interviewed, NbS are neither incorporated nor invested in.